2020
DOI: 10.1016/j.jctb.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Cuboids, a class of clutters

Abstract: The τ = 2 Conjecture, the Replication Conjecture and the f-Flowing Conjecture, and the classification of binary matroids with the sums of circuits property are foundational to Clutter Theory and have far-reaching consequences in Combinatorial Optimization, Matroid Theory and Graph Theory. We prove that these conjectures and result can equivalently be formulated in terms of cuboids, which form a special class of clutters. Cuboids are used as means to (a) manifest the geometry behind primal integrality and dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

7
0

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…In particular, every member of cuboid(S) has size n (hence cuboid(S) is a clutter) and τ (cuboid(S)) ≤ 2. Cuboids were introduced in [5] and further studied in [1].…”
Section: Cuboidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, every member of cuboid(S) has size n (hence cuboid(S) is a clutter) and τ (cuboid(S)) ≤ 2. Cuboids were introduced in [5] and further studied in [1].…”
Section: Cuboidsmentioning
confidence: 99%
“…Let conv(S) denote the convex hull of S. An inequality of the form ∑ i∈I x i + ∑ j∈J (1 − x j ) ≥ 1, for some disjoint I, J ⊆ [n], is called a generalized set covering inequality [8]. The set S is cube-ideal if every facet of conv(S) is defined by x i ≥ 0, x i ≤ 1, or a generalized set covering inequality [1].…”
Section: Cuboidsmentioning
confidence: 99%
“…We may assume that (p, q, r) = (1,2,3). Consider now the subcube of implying in turn that C has one of Q 3 , Q 6 as a cuboid minor.…”
Section: Proof Of Theorem 110 (I)mentioning
confidence: 99%
“…showed that these clutters possess a lot of structure, and his structure is qualitative in the sense that it explains why such clutters are non-ideal and do not pack. 1 Therefore, in light of the result above, we consider non-ideal mnp clutters well-understood, and focus on ideal mnp clutters.…”
Section: Introductionmentioning
confidence: 99%
“…A clutter C is binary if, for all members C 1 , C 2 , C 3 , the symmetric difference C 1 △C 2 △C 3 contains a member. 2 It can be readily checked that if a clutter is binary, then so is every minor of it [18,22]. It is known that a 1 A − B := {a ∈ A : a / ∈ B} 2 A 1 △ • • • △A k is the set of elements that belong to an odd number of the A i 's.…”
Section: Introductionmentioning
confidence: 99%